2015
DOI: 10.1371/journal.pone.0134230
|View full text |Cite
|
Sign up to set email alerts
|

Posture and Texting: Effect on Balance in Young Adults

Abstract: Using a mobile phone while doing another activity is a common dual-task activity in our daily lives. This study examined the effect of texting on the postural stability of young adults. Twenty college students were asked to perform static and dynamic postural stability tasks. Traditional COP and multivariate multiscale entropy (MMSE) were used to assess the static postural stability and the Star Excursion Balance Test (SEBT) was used to assess the dynamic postural stability. Results showed that (1) texting imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 27 publications
(50 reference statements)
4
33
0
Order By: Relevance
“…The studies that evaluated static postural stability used various entropy methods, such as Shannon entropy [9,62], Renyi entropy [9,62], approximate entropy [47,51,54,62], sample entropy [51,54,55,62,63], multiscale entropy [48][49][50]53,[56][57][58][59]61,62,65], composite multiscale entropy [62], and multivariate multiscale entropy [15,56], in order to find a better approach to evaluate human posture. The findings of the previous studies comparing entropy and traditional COP methods suggested that the entropy approach is more sensitive in characterizing sway [59] and gives higher reliability [55].…”
Section: Comparison Between Entropy Methods and Traditional Copmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies that evaluated static postural stability used various entropy methods, such as Shannon entropy [9,62], Renyi entropy [9,62], approximate entropy [47,51,54,62], sample entropy [51,54,55,62,63], multiscale entropy [48][49][50]53,[56][57][58][59]61,62,65], composite multiscale entropy [62], and multivariate multiscale entropy [15,56], in order to find a better approach to evaluate human posture. The findings of the previous studies comparing entropy and traditional COP methods suggested that the entropy approach is more sensitive in characterizing sway [59] and gives higher reliability [55].…”
Section: Comparison Between Entropy Methods and Traditional Copmentioning
confidence: 99%
“…Nurwulan et al used the entropy-based method along with the COP method to measure the effect of mobile phones on the static posture. To evaluate the effect on the dynamic posture, they compared the reaching distances with and without a secondary task [15].…”
Section: Primary Task Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Further, the SSI was developed to differentiate fallers and non-fallers. Conversely, the subjects in the current study were all healthy young adults with high adaptability to changes in the environment [3]. The performance accuracy could be higher if the acceleration data in all axes were considered and the subjects were not only healthy young adults [21].…”
Section: Resultsmentioning
confidence: 83%
“…Although this game is beneficial to encourage people to exercise, it is rather dangerous when people do not really pay attention to the road [1]. Mobile phone use during walking has a negative impact on working memory that increases perturbation that may cause accidents [2][3][4].…”
Section: Introductionmentioning
confidence: 99%